ANALISIS NILAI-NILAI BUDAYA DALAM NOVEL SI ANAK CAHAYA KARYA TERE LIYE - Pratiwi, Kelsy; Priyadi, Antonius Totok; Seli, Sesillia (Universitas Tanjungpura, 2023)
The objective of this study is to provide a description of the cultural values depicted in the novel Si Anak Cahaya by Tere Liye, as well as to examine the extent to which these cultural values are incorporated into the learning behavior of students studying Bahasa Indonesia at the senior high school level (SMA/MA). The employed research methodology is the descriptive method, specifically utilizing a approach. The methodology employed in this study is the sociological approach to literature. The primary data source utilized in this study is the literary work entitled